Analysis of leading edge flow characteristics in a mixed flow turbine under pulsating flows. (February 2019) - Lee, Samuel P; Jupp, Martyn L; Barrans, Simon M; Nickson, Ambrose K
Current trends in the automotive industry towards engine downsizing means turbocharging now plays a vital role in engine performance. A turbocharger increases charge air density using a turbine to extract waste energy from the exhaust gas to drive a compressor. Most turbocharger applications employ a radial inflow turbine. However, to ensure radial stacking of the blade fibers and avoid excessive blade stresses, the inlet blade angle must remain at zero degrees, creating large incidence angles. Alternately, mixed flow turbines can offer non-zero blade angles while maintaining radial stacking of the blade fibers and reducing leading edge separation at low velocity ratios. Furthermore, the physical blade cone angle introduced reduces the blade mass at the rotor outer diameter reducing rotor inertia and improving turbine transient response. The current paper investigates the performance of a mixed flow turbine under a range of pulsating inlet flow conditions. A significant variation in incidence across the LE span was observed within the pulse, where the distribution of incidence over the LE span was also found to change over the duration of the pulse. Analysis of the secondary flow structures developing within the volute shows the non-uniform flow distribution at the volute outlet is the result of the Dean effect in the housing passage. In-depth analysis of the mixed flow effect is also included, showing that poor axial flow turning ahead of the rotor was evident, particularly at the hub, resulting in modest blade angles. This work shows that the complex secondary flow structures that develop in the turbine volute are heavily influenced by the inlet pulsating flow. In turn, this significantly impacts the rotor inlet conditions and rotor losses.